2022
DOI: 10.1177/24730114221119754
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Analysis of Foot and Ankle Questions on the Orthopaedic In-Training Examination: A Guide for Resident Preparation

Abstract: Background: The Orthopaedic In-Training Examination (OITE) is a standardized examination administered annually to orthopaedic surgery residents. The examination is designed to evaluate resident knowledge and academic performance of residency programs. Methods: All OITE foot and ankle questions from 2009 through 2012 and 2017 through 2020 were analyzed. Subtopics, taxonomy, references, and use of imaging modalities were recorded. Results: There were a total of 167 foot and ankle (F&A)–related questions acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Because of this emphasis, trends in recent examination questions have been investigated to aid in preparation for the annual examination. 17,[19][20][21][22][23][24][25][26] Although several studies have shown a correlation between OITE performance and passing the Part I Certifying Exam, the validity of the OITE as a predictive measure for success on the Certifying Exam has been questioned because the two examinations have been written by separate organizations without a common blueprint. [27][28][29][30][31] A linking study found that on the 2021 AAOS OITE, the minimum OITE score that corresponded to passing the Part I Certifying Exam was 69.2%, but this was noted to be applicable to the 2021 OITE examination only.…”
Section: Resident Evaluation Tools Orthopaedic In-training Examinationmentioning
confidence: 99%
“…Because of this emphasis, trends in recent examination questions have been investigated to aid in preparation for the annual examination. 17,[19][20][21][22][23][24][25][26] Although several studies have shown a correlation between OITE performance and passing the Part I Certifying Exam, the validity of the OITE as a predictive measure for success on the Certifying Exam has been questioned because the two examinations have been written by separate organizations without a common blueprint. [27][28][29][30][31] A linking study found that on the 2021 AAOS OITE, the minimum OITE score that corresponded to passing the Part I Certifying Exam was 69.2%, but this was noted to be applicable to the 2021 OITE examination only.…”
Section: Resident Evaluation Tools Orthopaedic In-training Examinationmentioning
confidence: 99%